1995
DOI: 10.2214/ajr.165.3.7645474
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between benign and malignant adrenal masses: value of T1-weighted chemical-shift MR imaging.

Abstract: OBJECTIVE.Accuracy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
5

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(80 citation statements)
references
References 0 publications
1
74
0
5
Order By: Relevance
“…Because CT density values are related to tissue attenuation coefficients, fat containing structures will lower the measure ments of Hounsfield units more than other soft-tissuestructures, includingwater if fat is present in sufficient concentration. Korobkin et al [12] 18]. However, CT continues to remain the procedure of choice for evaluating adrenal massesbecauseof its widespread availability, high speed, and low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Because CT density values are related to tissue attenuation coefficients, fat containing structures will lower the measure ments of Hounsfield units more than other soft-tissuestructures, includingwater if fat is present in sufficient concentration. Korobkin et al [12] 18]. However, CT continues to remain the procedure of choice for evaluating adrenal massesbecauseof its widespread availability, high speed, and low cost.…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported quantitative or qualitative analysis of signal intensity loss in the adrenal lesions relative to reference tissues (liver, muscle, and spleen) on in-phase and opposed-phase sequences as means to differentiate adenomas from non-adenomas. The loss of signal on out-of-phase images in relation to spleen (to avoid the confounding of liver steatosis) differentiated adenomas from nonadenomas with a sensitivity of 84-100% and a specificity of 92-100% (37)(38)(39)(40). In general, adenomas appear as hypo-or iso-intense in comparison with the liver on T1-weighted images and hyper-or iso-intense to the liver on T2-weighted images.…”
Section: Epidemiologymentioning
confidence: 99%
“…Usually, malignant masses are hypointense on T1-weighted images and hyperintense on T2-weighted images, with strong enhancement after contrast injection and delayed washout. More recent studies have used the lipid content of adenomas, which causes a loss in signal intensity on chemical-shift MRI (Outwater et al 1995(Outwater et al , 1996. However, MRI may be helpful in the diagnosis of pheochromocytoma, where it outperforms CT scanning.…”
Section: Imaging Of Adrenal Incidentalomamentioning
confidence: 99%